Quality of life of Icelandic adolescents born with extremely low birthweight - Hólmdís Freyja Methúsalemsdóttir 1979- (2011)
Little is known about quality of life (QoL) of adolescents born with extremely low birthweight (ELBW <1000g). This study focuses on self-reported QoL of ELBW adolescents and how it compares with QoL of the general population. Increased knowledge of adolescents’ QoL is of special public health relevance since the adolescence years are the foundation for well-being and health in adulthood. This is a part of a national follow-up study on the long-term outcome of ELBW infants born in Iceland in 1991-1995. Total of 30 ELBW adolescents aged 14 - 19 years, and 30 controls with normal birthweight, matched on age and gender evaluated their QoL using an Icelandic version of KIDSCREEN-52, a generic self-reported questionnaire with scores in ten domains, each with mean = 50 and standard deviation = 10. To evaluate group differences Chi-square tests and Mann-Whitney U test were conducted. Multivariate logistic regression were used to study the influence of birthweight on QoL in ten dimensions each dichotomized into low (33% lowest values) and high QoL. ELBW adolescents reported lower QoL than matched controls; association was statistically significant on four dimensions: Physical well-being, Psychological well-being, Moods and emotion, and Self-perception with all odds ratios adjusted for gender. No differences were observed on Autonomy, Parent relation and home-life, Financial resources, Social support and peers, School environment and Social acceptance (bullying). This study shows that ELBW adolescents self-report their physical and emotional quality of life lower than their peers. Conversely social well-being and participation was reported similar among ELBW and normal birthweight adolescents. Lítið er vitað um lífsgæði unglinga sem fæddir eru sem litlir fyrirburar (< 1000 gr.). Í þessari rannsókn er greint frá lífsgæðum lítilla fyrirbura á unglingsárum og hvernig þau eru samanborið við lífsgæði jafnaldra. Aukin þekking á lífsgæðum unglinga hefur sérstakt gildi fyrir lýðheilsu þar sem unglingsárin eru grundvöllur ...